Paget’s disease of the breast: Our 20 years’ experience - Scardina, Lorenzo; Di Leone, Alba; Magno, Stefano; Franco, Antonio; Biondi, Ersilia; Sanchez, Alejandro Martin; D’Archi, Sabatino; Gentile, Damiano; Fabi, Alessandra; Masetti, Riccardo; Franceschini, Gianluca (Frontiers in Oncology, 2022)
Introduction Paget’s disease (PD) represents 1%–3% of all breast cancers and mostly occurs in postmenopausal women. Multiple studies have confirmed that breast-conserving surgery (BCS) followed by radiotherapy is a safe option for patients with in situ or invasive PD, ensuring local control and survival rates similar to those achieved with mastectomy. Materials and methods We retrospectively analyzed 115 patients affected by PD treated in our institution between January 2000 and May 2021. Median age at diagnosis was 60 years and median follow-up was 82 months; 69 patients were treated with BCS and 46 were treated with modified radical mastectomy or skin-sparing mastectomy. Results At histological examination, 59 patients (59/115, 51.0%) had an underlying invasive carcinoma; in 11 patients (11/115, 9.0%), only PD was found. In 45 patients (45/115, 40.0%), only noninvasive cancer was found. Nine patients (9/115, 7.8%) developed a local recurrence, 7 patients (7/115, 6.0%) are alive with distant metastasis, and 10 patients (10/115, 8.6%) died. Discussion In our series, no statistically significant differences were shown between PD alone, PD associated with in situ cancer, and PD with invasive cancer, regardless of the surgical procedure. BCS followed by radiotherapy appears to be an effective and safe option for patients with PD. Conclusion PD is a rare form of breast cancer and, in half of the cases, is associated with an invasive carcinoma. Separating our sample into three subgroups based on tumor histology, there were no significant differences in terms of LC, DFS, and OS rate in patients treated with different types of surgery. This study presents some limitations due to its retrospective nature and being confined to a single institution.